2012
DOI: 10.1016/j.ajhg.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SLC30A10 Cause Parkinsonism and Dystonia with Hypermanganesemia, Polycythemia, and Chronic Liver Disease

Abstract: Manganese is essential for several metabolic pathways but becomes toxic in excessive amounts. Manganese levels in the body are therefore tightly regulated, but the responsible protein(s) remain incompletely known. We studied two consanguineous families with neurologic disorders including juvenile-onset dystonia, adult-onset parkinsonism, severe hypermanganesemia, polycythemia, and chronic hepatic disease, including steatosis and cirrhosis. We localized the genetic defect by homozygosity mapping and then identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
415
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(428 citation statements)
references
References 24 publications
8
415
2
3
Order By: Relevance
“…Furthermore, patients carrying SLC39A14 mutations showed excessive Mn accumulation in the whole blood and brain but a lack of Mn in the liver, possibly due to the bypassing of hepatic uptake by Mn and subsequent biliary excretion in the absence of SLC39A14 (37). SLC30A10, a Mn exporter, is expressed in the liver and may be the transporter that excretes Mn from hepatocytes into the bile canaliculi (26). We have shown for the first time to our knowledge that ZIP8 is localized to the apical canalicular membrane of the hepatocyte and promotes the reuptake of Mn from the bile into the hepatocyte, thus acting to defend against Mn deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients carrying SLC39A14 mutations showed excessive Mn accumulation in the whole blood and brain but a lack of Mn in the liver, possibly due to the bypassing of hepatic uptake by Mn and subsequent biliary excretion in the absence of SLC39A14 (37). SLC30A10, a Mn exporter, is expressed in the liver and may be the transporter that excretes Mn from hepatocytes into the bile canaliculi (26). We have shown for the first time to our knowledge that ZIP8 is localized to the apical canalicular membrane of the hepatocyte and promotes the reuptake of Mn from the bile into the hepatocyte, thus acting to defend against Mn deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Mn deficiency impairs bone formation, fertility, and the metabolism of glucose, lipids, and carbohydrates (20,23). Despite the essentiality of Mn, only divalent metal transporter 1 (DMT1) (24,25) and SLC30A10 (25,26) have been established as Mn transporters in vivo, and the physiological regulation of Mn metabolism is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic studies identified mutations in the human gene that were associated with hypermanganesemia. Loading of this metal is observed in both tissues, resulting in cirrhosis of the liver and Parkinson-like motor impairments (94,95). Due to the roles of manganese (and zinc) in combating infection, one speculation is that this transporter may also participate in the host immune response.…”
Section: Roles Of Other Transportersmentioning
confidence: 99%
“…For example, toxic effects of hypermanganesemia are seen in an inherited Mn overload syndrome associated with genetic defects in SLC30A10 (15,16). Recent studies have shown that SLC30A10 is a cell surfacelocalized Mn efflux transporter that reduces cellular Mn levels and protects against Mn toxicity (17,18).…”
mentioning
confidence: 99%